2019
DOI: 10.1017/s0954579419000233
|View full text |Cite
|
Sign up to set email alerts
|

Development of attention from birth to 5 months in infants at risk for autism spectrum disorder

Abstract: Social-communication skills emerge within the context of rich social interactions, facilitated by an infant's capacity to attend to people and objects in the environment. Disruption in this early neurobehavioral process may decrease the frequency and quality of social interactions and learning opportunities, potentially leading to downstream deleterious effects on social development. This study examined early attention in infant siblings of children with autism spectrum disorder (ASD) who are at risk for socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…Social attention deficits at different ages may also vary along the developmental trajectory of ASD. Finally, there may be a distinction between diagnostic and phenotypic biomarkers, such that some tasks are more sensitive to the potentially binary diagnostic classification of ASD, whereas other tasks are more sensitive to the phenotypic heterogeneity observed within ASD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social attention deficits at different ages may also vary along the developmental trajectory of ASD. Finally, there may be a distinction between diagnostic and phenotypic biomarkers, such that some tasks are more sensitive to the potentially binary diagnostic classification of ASD, whereas other tasks are more sensitive to the phenotypic heterogeneity observed within ASD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the phenotypic heterogeneity in ASD, eye tracking might be an objective way to assess social attention [ 2 ] wherein social attention differences have been noted in infant siblings of children with ASD, as well as toddlers, children, and adults with ASD, compared to individuals without ASD [ 3 8 ]. Current evidence suggests it may be possible to predict social-communicative outcomes and risk for ASD based on early visual attention to social stimuli, highlighting social attention as a potential predictive biomarker for ASD [ 9 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous research including HR-Sibs suggests that atypically shorter spontaneous fixations to nonsocial stimuli may already be present at 6–9 months (Wass et al, 2015), whereas longer latencies to disengage attention from similar stimuli become more apparent at approximately 10–14 months of age (Elison et al, 2013; Elsabbagh et al, 2013). Recent research has also suggested that disrupted patterns of visual attention to social stimuli (e.g., human faces or social scenes) may already be present by 6 months of life, perhaps even earlier (Bradshaw et al, 2020). We take these previous findings, and similar others (Chawarska, Macari, & Shic, 2013; Sacrey, Bryson, & Zwaigenbaum, 2013), to suggest that supporting the development of self-regulated attention and associated brain networks (e.g., reorienting system; (Corbetta, Patel, & Shulman, 2008) in very young children with ASD or early emerging features of ASD is a key intervention target.…”
Section: Self-regulated Attention As a Therapeutic Target And Mechanimentioning
confidence: 99%
“…By three months of age, social gaze is the primary modality of coordinated interactions, occurring 30–50% of the time in low risk infants. But attention to eyes declines between 2 and 6 months in infants who later develop ASD (Jones and Klin, 2013), and high-risk siblings perform lower on visual attention tasks at 2 and 3 months of age compared to low-risk infants (Bradshaw et al, 2019).…”
Section: The First 100 Days Post-term: Window Of Critically Injury-sementioning
confidence: 99%